Stochastic demethylation and redundant epigenetic suppressive mechanisms generate highly heterogeneous responses to pharmacological DNA methyltransferase inhibition - Mie K. Jakobsen; Sofie Traynor; Aaraby Y. Nielsen; Christina Dahl; Mette Staehr; Simon T. Jakobsen; Maria S. Madsen; Rasmus Siersbaek; Mikkel G. Terp; Josefine B. Jensen; Christina B. Pedersen; Anup Shrestha; et al. (Journal of Experimental & Clinical Cancer Research, 2025)
Abstract Background Despite promising preclinical studies, the application of DNA methyltransferase inhibitors in treating patients with solid cancers has thus far produced only modest outcomes. The presence of intratumoral heterogeneity in response to DNA methyltransferase inhibitors could significantly influence clinical efficacy, yet our understanding of the single-cell response to these drugs in solid tumors remains very limited. Methods In this study, we used cancer/testis antigen genes as a model for methylation-dependent gene expression to examine the activity of DNA methyltransferase inhibitors and their potential synergistic effect with histone deacetylase inhibitors at the single-cancer cell level. The analysis was performed on breast cancer patient-derived xenograft tumors and cell lines, employing a comprehensive set of techniques, including targeted single-cell mRNA sequencing. Mechanistic insights were further gained through DNA methylation profiling and chromatin structure analysis. Results We show that breast cancer tumors and cell cultures exhibit a highly heterogenous response to DNA methyltransferase inhibitors, persisting even under high drug concentrations and efficient DNA methyltransferase depletion. The observed variability in response to DNA methyltransferase inhibitors was independent of cancer-associated aberrations and clonal genetic diversity. Instead, these variations were attributed to stochastic demethylation of regulatory CpG sites and the DNA methylation-independent suppressive function of histone deacetylases. Conclusions Our findings point to intratumoral heterogeneity as a limiting factor in the use of DNA methyltransferase inhibitors as single agents in treatment of solid cancers and highlight histone deacetylase inhibitors as essential partners to DNA methyltransferase inhibitors in the clinic.